Biochemical Pathways of Sarcopenia and Their Modulation by Physical Exercise: A Narrative Review - Ziaaldini, Mohammad Mosaferi; Marzetti, Emanuele; Picca, Anna; Murlasits, Zsolt (Frontiers in Medicine, 2017)
Aging is a complex process characterized by progressive multisystem derangement predisposing individuals to increased risk of developing negative health outcomes. Sarcopenia is the age-related decline of muscle mass and function/strength and represents a highly prevalent correlate of aging. Several factors have been indicated to play a role in the onset and progression of sarcopenia; however its pathophysiology is still unclear. Physical exercise is to date one of the few strategies able to improve muscle health in old age through multiple metabolic and transcriptional adaptations. Although, the benefits of different exercise modalities on the function and structure of aged myocytes is acknowledged, the cellular and molecular mechanisms underlying such effects are not yet fully identified. Here, we briefly overview the current knowledge on the biochemical pathways associated with the onset and progression of sarcopenia. We subsequently describe the effects of exercise on relevant signaling pathways involved in sarcopenia pathophysiology.